ChemInform Abstract: Ring‐Opening, Cycloaddition and Rearrangement Reactions of Nitrogen‐Substituted Cyclopropane Derivatives. Issue 36 (August 2016) - Rassadin, Valentin A.; Six, Yvan
Abstract: Review: 385 refs.